AlGaN/GaN Heterostructure Schottky Barrier Diodes with Graded Barrier Layer. (6th April 2022) - Liu, Honghui; Liang, Zhiwen; Yan, Chaokun; Liu, Yuebo; Wang, Fengge; Xu, Yanyan; Shen, Junyu; Xiao, Zhengwen; Wu, Zhisheng; Liu, Yang; Wang, Qi; Wang, Xinqiang; et al.
Abstract : The AlGaN/GaN Schottky barrier diodes (SBDs) working as high-power mixer and multiplier show great potential in millimeter wave (MMW) field owing to their high breakdown voltage. Nevertheless, its further application is severely limited by large reverse leakage current ( J r ) since the two-dimensional electron gas (2DEG) channel is hard to be pinched off at low voltage. To address this limitation, a graded AlGaN/GaN heterostructure is introduced to extend the 2DEG channel into a quasi-three-dimensional electron slab. By comparing the fixed Al composition AlGaN/GaN SBD, J r of the graded AlGaN/GaN SBD is significantly reduced due to the extension of channel carriers, confirming the effective J r suppression effect of this structure. Furthermore, on this basis, a recessed anode structure is utilized to expect a smaller J r . The results indicated that the graded AlGaN/GaN SBDs with air-bridge structure have achieved a pretty low J r value (1.6 × 10 −13 A at -15 V), and its cutoff frequency is as high as 60.6 GHz. It is expected that such SBDs with low J r have significant advantages in future applications.